Reliability of some tinnitus psychoacoustic measures - Daoud, Elza; Enzler, Falco; Fournier, Philippe; Noreña, Arnaud J. (Frontiers in Audiology and Otology, 2024)
Introduction Psychoacoustic measures are used to quantify tinnitus perception in clinical and research settings. Residual inhibition (RI), for instance, is defined as a temporary reduction in tinnitus loudness after the presentation of an acoustic stimulus. A novel approach was developed recently to assess the minimum sound level producing RI, the minimum residual inhibition level (MRIL), after the repeated presentation of short sounds separated by short periods of silence. Two studies were performed: the objective of the study 1 was to assess the reliability and the reproducibility of this measures as well as others, including the minimum masking level (MML). The objective of study 2 was to assess whether a smoother envelope of the sound would produce similar levels of MML and MRIL and improve listening comfort. Methods Thirty participants with chronic tinnitus completed each study. For study 1, MML and MRIL were obtained at the seven standard audiometric frequencies at around 1-month interval. For study 2, MML and MRIL were obtained using triangular and trapezoidal-shaped NBN signals centered at three different frequencies. Results The mean absolute test-retest difference was 3 dB for both MML and MRIL [Intraclass correlation, ICC (2,1) of 0.70 and 0.84, respectively] for the measures obtained in test and retest (86% of cases for MML and 21% of cases for complete MRIL). While the two types of envelopes provided comparable MRIL, the “triangular” envelope provided more listening comfort. Discussion In sum, the novel approach provides quick and reliable MML and MRIL measurement, with the potential benefit of subtyping participants.